Physicochemical Characterization of Quinoa (Chenopodium quinoa cv. Nariño) Co-products Obtained by Wet Milling - Ortiz-Gómez, Vicente; Fernández-Quintero, Alejandro; Roa-Acosta, Diego Fernando; Bravo-Gómez, Jesús Eduardo; Solanilla-Duque, Jose Fernando (Frontiers in Sustainable Food Systems, 2022)
In recent years, great interest has been shown in pseudocereals for their high nutritional value. Wet milling has been used to obtain macromolecules such as proteins and starches. However, the co-products obtained from this food industry have been studied little. A factorial design Box-benhken was used to study the effect of surfactant concentration (SDS), sodium hydroxide (NaOH) concentration and maceration temperature on structural and colorimetric properties. Structural properties were evaluated by infrared spectroscopy (FTIR-ATR) and color changes by the CIElab tristimulus method (L*, a*, b*). A decrease in temperature and NaOH causes a decrease in lightness (L*), resulting in lower starch content and higher protein content in the co-product. This behavior was correlated with the infrared spectroscopy (FTIR-ATR) spectra. The spectra show a possible structural change in the amylose/amylopectin ratio of the starch granule at 1012 cm-1, 1077 cm-1 and 1150 cm-1 bands, which are associated with glycosidic bonds, these bonds were sensitive to NaOH concentration. While those bands assigned to Amide II (1563 cm-1) and Amide I (1633 cm-1), were sensitive to the effect of NaOH and maceration temperature, evidencing that protein content in the co-products is variable and depends significantly on the extraction conditions. The co-products obtained by wet milling could be used in the development of functional foods, such as bread, snacks, pasta and other products.